Analysis Of The Influence Of Perception Of Usefulness, Perception Of Ease And Perception Of Risk On The Interest Of Msmes To Transact Using Fintech/Financial Technology As A Digital Payment Service (Study on MSMEs in Nganjuk Regency) - Rosmayanti, Fitri; Santo Hegiarto, Aldy (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to determine what factors can influence Repurchase interest. This study uses three independent variables Product Quality (X1), Service Quality (X2), and Price (X3). Meanwhile, Repurchase (Y) is used as the dependent variable. In this study, the authors used descriptive-quantitative research methods, namely researchers tried to make a description, description systematically, factually and accurately regarding the relationship between the facts, characteristics or phenomena studied. The R Square coefficient is 0.742, or 74.2%, which indicates that the variables of Product Quality (X1), Service Quality (X2), and Price (X3) affect the Repurchase Decision variable by 74.2%, other variables not included in this study affect 25.8% of the total. Repurchase simultaneously or simultaneously has a positive effect between Product Quality, Service Quality and Price with Repurchase interest. This is indicated by the calculated F value of 50,553 and significance at <0.001, so with these results indicating that Product Quality, Service Quality and Price are not simultaneously due to the positive influence of several elements that make a significant contribution to the Repurchase of Some More Taste Swits